2008
DOI: 10.1074/jbc.m803649200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Significance of the Interaction between the mRNA-binding Protein, Nab2, and the Nuclear Pore-associated Protein, Mlp1, in mRNA Export

Abstract: Nuclear export of mRNA requires several key mRNA-binding proteins that recognize and remodel the mRNA and target it for export via interactions with the nuclear pore complex. In Saccharomyces cerevisiae, the shuttling heterogeneous nuclear ribonucleoprotein, Nab2, which is essential for mRNA export, specifically recognizes poly(A) RNA and binds to the nuclear pore-associated protein, myosin-like protein 1 (Mlp1), which functions in mRNA export and quality control. Specifically, the N-terminal domain of Nab2 (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 67 publications
(80 reference statements)
6
85
0
1
Order By: Relevance
“…Strikingly, ;50% (114/220) of the RNA-dependent binders we identified were already known to be RBPs (enrichment P-value 2 3 10 À35 ), which is a considerable improvement over previous approaches. The RBP Nab2 is involved in the end processing, polyadenylation, and export of poly(A) mRNA from the nucleus; we see both known and novel RNAdependent interactions with Nab2 that are consistent with the existing model (Hector et al 2002;Tran et al 2007;Fasken et al 2008;Iglesias and Stutz 2008;Tutucci and Stutz 2011). However, our data provide new insight into the temporal program of Nab2 binding based on evidence for concurrent binding with RBPs involved in transcription, splicing, and translation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Strikingly, ;50% (114/220) of the RNA-dependent binders we identified were already known to be RBPs (enrichment P-value 2 3 10 À35 ), which is a considerable improvement over previous approaches. The RBP Nab2 is involved in the end processing, polyadenylation, and export of poly(A) mRNA from the nucleus; we see both known and novel RNAdependent interactions with Nab2 that are consistent with the existing model (Hector et al 2002;Tran et al 2007;Fasken et al 2008;Iglesias and Stutz 2008;Tutucci and Stutz 2011). However, our data provide new insight into the temporal program of Nab2 binding based on evidence for concurrent binding with RBPs involved in transcription, splicing, and translation.…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, there is a >95% chance that Yhr097c cross-links with higher efficiency than the negative controls. Nab2 is involved in the end processing, polyadenylation, and export of poly(A) mRNA from the nucleus (Green et al 2002;Hector et al 2002;Fasken et al 2008;Iglesias and Stutz 2008;Tutucci and Stutz 2011). It is generally believed that Nab2 binds to mRNAs during their end cleavage and polyadenylation and is removed immediately following their nuclear export (Lee and Aitchison 1999;Tran et al 2007).…”
Section: Identification and Validation Of Novel Rna-binding Proteinsmentioning
confidence: 99%
“…This is of interest since Mex67 is the Nxf1 yeast ortholog and has been shown to be a major mRNA export factor (Segref et al 1997;Katahira et al 1999). Mlp1 has also been shown to interact with Nab2, a poly(A)-binding protein that also interacts with Mex67 (Green et al 2003a;Fasken et al 2008). Currently, no definitive mammalian ortholog for Nab2 has been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Nab2 is mainly localized in the nucleus (7,8) and interacts with the poly(A)-binding protein (Pab1) to affect poly(A) tail length (9). Moreover, Nab2 interacts with Mlp1, a nuclear pore complex-associated protein at the nuclear basket involved in mRNP quality control (10), with Gfd1 and Gle1, factors involved in mRNA export (11), and with the Sac3-Thp1 complex, which plays a role in coupling transcription with mRNA metabolism (12). When the pools of mRNAs immuneprecipitated by Npl3, Nab2, and Nab4 were determined in microarrays and compared, it was suggested that distinct sets of mRNAs are bound to each of these proteins (13).…”
mentioning
confidence: 99%